THE MAKING OF LIQUID ORGANIC FERTILIZER FROM GINGER WASTE BY HIGH SCHOOL STUDENTS AT AL HIDAYAH DLANGGU MOJOKERTO - Yusuf, Ah; Rizki Fitryasari; Kotijah, Siti; Manalu, Novita Verayanti; Nayluzzuharo', Fanny; Verantika Setya Putri; Sumiatin, Titik; Surya, Ronal (Universitas Airlangga, 2024)
Introduction: After the production of